2022
DOI: 10.3748/wjg.v28.i48.6909
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor erythroid 2-related factor 2-mediated signaling and metabolic associated fatty liver disease

Abstract: Oxidative stress is a key driver in the development and progression of several diseases, including metabolic associated fatty liver disease (MAFLD). This condition includes a wide spectrum of pathological injuries, extending from simple steatosis to inflammation, fibrosis, cirrhosis, and hepatocellular carcinoma. Excessive buildup of lipids in the liver is strictly related to oxidative stress in MAFLD, progressing to liver fibrosis and cirrhosis. The nuclear factor erythroid 2-related factor 2 (NRF2) is a mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 83 publications
(80 reference statements)
0
18
0
Order By: Relevance
“…CAP, a natural small molecule derived from chili peppers, has been identified and verified to modulate the KEAP1-NRF2-ARE pathway in our study. This signaling plays a key role in several cancerous and non-cancerous diseases [33][34][35][36][37] . Therefore, it is a promising therapeutic target for combatting free radical damage associated with numerous conditions, including Alzheimer's disease 38 , chronic kidney disease 39 , cardiovascular disease 40 , cancer and aging 41 .…”
Section: Discussionmentioning
confidence: 99%
“…CAP, a natural small molecule derived from chili peppers, has been identified and verified to modulate the KEAP1-NRF2-ARE pathway in our study. This signaling plays a key role in several cancerous and non-cancerous diseases [33][34][35][36][37] . Therefore, it is a promising therapeutic target for combatting free radical damage associated with numerous conditions, including Alzheimer's disease 38 , chronic kidney disease 39 , cardiovascular disease 40 , cancer and aging 41 .…”
Section: Discussionmentioning
confidence: 99%
“…36 Nrf2 plays an important role in neutralizing oxidative stress and conserving redox homeostasis in the cell through the generation of cytoprotective and antioxidant enzymes, such as HO-1 and NQO1. 37 The role of Nrf2 in liver steatosis, inflammation, fibrosis, as well as related therapeutic strategies has been recently summarized by Bukke et al 38 Besides, the studies that the natural plants components alleviate NAFLD via AMPK/Nrf2 pathway have been reported extensively. 36,39,40 In this study, the downregulation in the relative protein level of p-AMPK/AMPK, Nrf2, and HO-1 in HFD-feeding rats was restored by the treatment of PMS, suggesting that PMS activated the AMPK/Nrf2 pathway in HFD-induced NAFLD rats.…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
“…Nuclear factor erythroid 2-related factor 2 (NRF2) plays a central role in the regulation of cellular defense mechanisms against environmental stresses, especially in maintaining liver REDOX homeostasis under oxidative stress. 19 Additionally, the transcription activation of two-phase detoxification and antioxidant enzymes, including thioredoxin reductase (TrxR), thioredoxin (Trx), glutathione reductase (GR), glutaredoxin (Grx), glutathione S-transferase (GST), and glutathione peroxidase (GPx), can clear cellular oxidative stress and maintain REDOX balance. 20 Previous studies demonstrated that moderate reactive oxygen species (ROS) generated using EGCG (55 mg kg −1 ) by intraperitoneal injection (i.p.)…”
Section: Introductionmentioning
confidence: 99%